Enhancing the mechanical properties of cross-linked rubber-toughened nanocomposites via electron beam Irradiation - Jamal, Nur Ayuni; Anuar, Hazleen; Abd Razak, Shamsul Bahri (Hindawi Publishing Corporation, 2011)
Improving the mechanical properties of a pristine system is the main target of developing nanocomposites. The nanocomposites systems were first prepared via intercalation technique with different organophilic montmorillonite (OMMT) loading. Two types of cross-linking techniques were applied, namely, as maleic anhydride polyethylene (MAPE) and electron beam (EB) irradiated system. The effectiveness of these systems was then compared with the control one and analyzed based on the mechanical tests and morphological examination. The mechanical tests revealed that control, MAPE, and EB irradiated systems had attained the optimum mechanical properties at 4 vol% OMMT content. EB irradiated unit of a dose of 100 kGy showed excellent mechanical properties with higher crosslinking degree which were proved by gel content analysis. X-ray diffraction (XRD) analysis confirmed the existence of delamination structure with MAPE and EB irradiation techniques based on the disappearance of characteristic peak. The degree of delamination was further investigated by transmission electron microscope (TEM).